A feasibility study of pulmonary nodule detection by ultralow-dose CT with adaptive statistical iterative reconstruction-V technique. Issue 119 (October 2019) - Ye, Kai; Zhu, Qiao; Li, Meijiao; Lu, Yuliu; Yuan, Huishu
Highlights: The mean effective radiation dose of ultralow-dose CT(ULDCT) was 0.096mSv. Image quality of ULDCT with ASiR-V can meet the diagnostic requirements. The ULDCT has high sensitivity for pulmonary nodule detection with diameter≥6 mm. ULDCT is an effective method for measurement of the diameter of pulmonary nodules. BMI with values<30 kg/m 2 has no effects on the detection rate of pulmonary nodules. Abstract: Purpose: To evaluate the clinical value of ultralow-dose CT (ULDCT) with adaptive statistical iterative reconstruction-V (ASiR-V) in the detection of pulmonary nodules in a Chinese population. Method: One hundred eighty-eight patients (16.41 ≤ BMI ≤ 29.87 kg/m 2 ) with pulmonary nodules detected on low-dose chest CT (LDCT) underwent local ULDCT at the center of the chosen nodule with a scan length of 3 cm. LDCT was performed using the Assist kV (120/100 kV)/Smart mA mode and at 120 kV/2.8 mAs for ULDCT. After scanning, CT images were reconstructed with ASiR-V 50%. For both scans, nodule diameters were measured and reference standards were established for the presence and types of lung nodules found on LDCT. The sensitivity of ULDCT was compared against the standard, and logistic regression analysis was used to determine the independent predictors for nodule detection. Results: Compared with LDCT (0.93 ± 0.32 mSv), a 89.7% dose decrease was seen with ULDCT, for which the calculated effective dose was 0.096 ± 0.006 mSv (P < 0.001). LDCT showed 188 nodules, including 123 solid and 65 subsolid nodules. The overall sensitivity for nodule detection in ULDCT was 90.4% (170/188), and 98.2% (54/55) for nodules ≥ 6 mm. In multivariate analysis, nodule types and diameters were independent predictors of sensitivity (P < 0.05). However, patients' BMI had no effect on nodule detection (P > 0.05). Conclusions: ULDCT can be used in the management of pulmonary nodules for people with BMI ≤ 30 kg/m 2 at 10% radiation dose of LDCT.